A Bibliometric Analysis of Studies on Cultural Preservation, Youth Engagement, and the Seren Taun Ceremony - Khairani, Salsabila; Setiadi, Elly Malihah; Komariah, Siti (Mimbar Agama Budaya, 2025)
Cultural preservation is a crucial effort to maintain national identity while confronting the challenges of globalization, which have the potential to erode local wisdom values. This study aims to map the development of academic studies on cultural preservation, particularly regarding local wisdom, youth generation, and the Seren Taun ceremony. The method used is bibliometric analysis with Publish or Perish (PoP), collecting data from Google Scholar for the period 2015–2025. Eighty articles were analyzed using VOSviewer to generate three types of visualizations: network, overlay, and density. The results show a significant upward trend in publications, with the highest number in 2025. Network visualization analysis identified four main clusters dominated by cultural heritage, local wisdom, community, and tradition, while Seren Taun appeared fragmented. The overlay visualization showed that the issues of the youth generation and Seren Taun emerged prominently during 2023–2025, indicating a shift in research focus. Density visualization represented high density in Indonesia, local wisdom, and Seren Taun, but the involvement of the youth generation and the term cultural preservation remained restricted. These findings identify a research gap in the roles of youth in cultural preservation, specifically in the context of the Seren Taun ceremony. This study is expected to provide an overview of the research map and direction for the development of more participatory and contextual cultural research in the future.